Examining the Efficacy of Fishbowl Simulation in Preparing to Teach English Learners in Secondary Schools - Liu, Kimy; McFarland, Jon (Frontiers in Education, 2021)
During the COVID-19 crisis, teacher educators are grappling to provide teacher candidates meaningful field experiences to serve English learners (ELs) during campus closures. The purpose of this study was to explore teacher candidates’ beliefs on second language acquisition (SLA) in the context of teaching ELs in secondary schools. Multiple data sources were used to evaluate fishbowl simulations’ efficacy as a viable alternative to gain meaningful field experience. Findings suggest strong connections between participants’ beliefs and their chosen instructional moves, with participants realizing the importance of meaning-making. Teacher candidates and teacher educators gain unique insight on effectively teaching and implementing SLA strategies with educational simulations.